Pengaruh Penguatan Oleh Guru Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti di SMP Negeri 4 Laguboti, Kabupaten Toba T.A. 2023/2024 - Lamria Junita Sihombing; Jungjungan Simorangkir; Andrianus Nababan; Wilson Simanjuntak; Andar Gunawan Pasaribu (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to find out how much positive and significant influence teacher reinforcement has on the learning motivation of students at SMP Negeri 4 Laguboti, Toba Regency, T.A 2023/2024. The research method used is descriptive and inferential quantitative methods. The population is all students in class VIII at SMP N 4 Laguboti, 2023/2024 academic year as many as 159 people and a sample of 33 people was determined using a probability sampling technique with a random type (simple random sampling). Data was collected using a positive closed questionnaire with 38 items, namely 14 items for variable 2024: 1) Test analysis requirements: a) positive relationship test obtained by rxy = 0.483 > rtable(a=0.05,n=33) = 0.344. b) Testing a significant relationship obtained tcount= 3.072 > ttable(a=0.05,dk=n-2=31)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation Y=39.70+0.89X. b) Regression coefficient of determination test (r2) = 23.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(a=0.05, dk numerator k=12, dk denominator=n-2=33-2=31) namely 9.43 > 2.09. Thus Ha is accepted and H0 is rejected. It can be concluded that maximum teacher reinforcement can increase students' learning motivation in Christian religious education and character subjects at SMP Negeri 4 Laguboti, Toba Regency T.A. 2023/2024